Exclusive and inclusive semileptonic decays of B mesons to D mesons - FULTON, R. (Institutional Knowledge at Singapore Management University, 1991)
We report new measurements of the branching fractions B ( B − → D 0 l − ¯ ν ) , B ( ¯ B 0 → D + l − ¯ ν ) , and B ( B − → D * 0 l − ¯ ν ) . Combining these results with our previous measurement of B ( ¯ B 0 → D * + l − ¯ ν ) , we find that the ratio of semileptonic widths for final states with a vector meson and pseudoscalar meson is ( 2.6 + 1.1 + 1.0 − 0.6 − 0.8 ) and the ratio of charged- to neutral- B -meson lifetimes is ( 0.89 ± 0.19 ± 0 . 1 3 ) ( f 00 f + − ) where ( f 00 f + − ) is the ratio of neutral- to charged- B -meson production at the Υ ( 4 S ) . From the ¯ B → D l − ¯ ν branching fraction, we calculate | V cb | = 0.040 ± 0.006 ± 0.006 , where the first error is statistical and the second is systematic and dominated by the uncertainty in the B -meson lifetime.